2019
DOI: 10.1002/hed.25873
|View full text |Cite
|
Sign up to set email alerts
|

Timing of surgery and adjuvant radiation therapy for sinonasal malignancies: Effect of surgical approach

Abstract: Background Timely postoperative radiation therapy (RT) within 50 days of surgery for head and neck cancers provides a survival advantage. Methods Using the National Cancer Database, we performed a propensity score‐matched analysis comparing patients undergoing open or endoscopic surgery for squamous cell carcinoma (SCC) of the nasal cavity and paranasal sinuses from 2010 to 2015. Results Among 168 pairs, patients undergoing endoscopic surgery had shorter time to surgery (24.2 vs 36.7 days, P < .001) and shorte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…20 Other studies have shown that delays in beginning adjuvant radiotherapy after surgery lead to increased mortality. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…20 Other studies have shown that delays in beginning adjuvant radiotherapy after surgery lead to increased mortality. 21,22…”
Section: Discussionmentioning
confidence: 99%
“…The debate on whether endoscopic or open surgery should be selected has been slowly progressing towards consensus. There is evidence that endoscopic transnasal surgery provides a shorter hospital stay [ 83 ] and surgery-to-radiation time [ 84 ]. The belief that complications rate was higher for open surgery was instead recently tempered by a meta-analysis [ 85 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Timely co-ordination between surgeons and radiation oncologists is strongly recommended when a patient affected by SNSCC has to undergo a multimodal treatment. In fact, it has been recently demonstrated that surgery-to-radiation interval should be kept within 61 days to avoid outcomes worsening [ 84 ].…”
Section: Treatmentmentioning
confidence: 99%
“…For example, some authors suggest that radiotherapy should be performed 3 months after surgery to allow healing after craniofacial resection [48]. Endoscopic surgery, therefore, reduces this time, reducing the delay to 15 days between diagnosis and radiotherapy compared to craniectomy surgery, in a series of 168 patients matched on the National Cancer DataBase (NCDB) [49]. Different studies comparing the oncological results between the transfacial and endoscopic approaches have shown similar results in terms of survival [46,[50][51][52].…”
Section: Oncological Resultsmentioning
confidence: 99%